Geochemistry of five sediment sequences obtained in the Campo coastal plain on Elba Island (Tuscany, Italy) - Fabian Becker; Raphael Eser; Philipp Hoelzmann; Brigitta Schütt (PANGAEA, 2018)
We obtained five sediment sequences by percussion drilling in order to reconstruct human-landscape interactions in the context of ancient bloomery smelting on Elba Island, Tyrrhenian Sea, based on sedimentological evidences; Elba was, together with Populonia, the centre of iron production in antiquity (mid-6th century B.C.E. to 2nd century C.E.). The aim of the analysis is an assessment of (1) palaeolandscape site conditions, (2) morphodynamics triggered by human land use change (especially charcoal production to run the bloomeries); and (3) to characterize a sediment smelting signature. We described the sediments macroscopically and measured basic bulk geochemical parameters, including pH, electric conductivity, total organic and inorganic carbon contents (estimated using LOI at 560 °C and 900 °C), magnetic susceptibility, and sediment colour. The element composition of the sediment sequences was obtained by ICP-OES, portable ED-XRF, and a CHN+S analyser. Geochemical units ( extquotesinglechemofazies extquotesingle) were grouped by cluster analysis in a compositional-data framework.
Supplement to: Becker, F et al. (2019): Reconstructing human–landscape interactions in the context of ancient iron smelting on Elba Island, Italy, using sedimentological evidence. Geoarcheology, 34(3), 336-359, https://doi.org/10.1002/gea.21726